Analysis of Millennial Muslims Preferences on the Crowdfunding Platform - Muhammad Zacky Dzulfikar; Purbayu Budi Santosa; Eddy Yusuf Agung Gunanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The potential for collecting alms funds in Indonesia is very large, the trend of increasing the collection of Zakat Infaq Alms (ZIS) funds until 2019, as well as the increasing trend of collecting donations through digital crowdfunding platforms. In fact, the potential for collecting ZIS is only 4.91% of the existing potential, besides that there are still many donations from crowdfunding platforms that have not yet reached the target, then millennials as the majority generation and close to technology in the digital era 4.0, are faced with the choice of giving traditional or traditional charity. through a crowdfunding platform. The research analyzes the preferences of millennial Muslims in giving charity on the crowdfunding platform. The population in this research, millennial Muslims in Semarang City. The sampling technique of non-probability sampling is purposive sampling, taking this samples from populations that must have certain requirements. Sampling of data was done by distributing questionnaires to 384 millennial Muslim respondents in the city of Semarang. The research method uses binary logistic regression analysis. The results of the research simultaneously show the influence of millennial Muslim decisions to give alms on the crowdfunding platform. Partially there is a positive and significant influence on the motivational variables of religiosity, effort expectancy, sense of trust, social influence, and lifestyle on the decision of millennial Muslims to give alms on the crowdfunding platform. The income variable has no effect on the decision of millennial Muslims to give alms on the crowdfunding platform.